La comunicación familiar y el consumo de alcohol de los adolescentes del segundo año de bachillerato del colegio nacional “Adolfo Valarezo”, de la ciudad de Loja, 2013 - Gualán Condolo, Luis Enrique (2014)
This research entitled: Family communication and consumption of alcohol by adolescents Second Year of National College Baccalaureate "Adolfo Valarezo" city of Loja, 2013, was formulated as general objective to analyze the influence of family communication in the alcohol consumption of students surveyed. We used a descriptive study in a population of 134 students. The technique and instruments used was the survey, the instrument applied Scale Communication between parents and sons / daughters (CA-M/CA-P) Barnes and Olson (1992) and the Test of AUDIT (Alcohol Use Disorders Identification), which allowed assessing alcohol dependence. The main findings were that 71.64% of the investigated express low levels of offending communication, and 67.91% in medium levels maintain avoidant communication. On the consumption of alcohol: 58.96% do not have a problem with alcohol, whereas 27.61% of the populations are starting to show signs of alcohol abuse. Conclusions: The vast majority of students report that parent-child communication at low levels is mildly offensive and avoidant. That the highest percentage of surveyed do not have serious problems with alcohol, without knowing that there are minimum percentages show signs of problems in consumption. That type of offensive communication that parents keep children at low levels and avoidant communication medium influences in alcohol consumption in the population studied.